COMBINING OF CHRONIC BRONCHITIS AND GASTROESOPHAGEAL REFLUX DIESEASE IN PULMONOLOGIST PRACTISE - Шевчук-Будз, У. І.; Островський, М. М.; Філіпова, С. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The detailed description of clinical motion of the united pathology is resulted in the article. The sources of literature are analyzed from the given diseases.